Tooth and claw ebook - Johnson, Craig (Walt Longmire Mystery, 2024)
In the tradition of Wait for Signs and The Highwayman , Craig Johnson is back with a short novel set in the Alaska tundra where a young Walt Longmire and Henry Standing Bear face off with powerful enemies who will do anything to get what they want. Tooth and Claw follows Walt and Henry up to Alaska as they look for work after they both returned from serving in Vietnam. While working for an oil company in the bitter cold of winter, they soon encounter a ferocious polar bear who seems hell-bent on their destruction. But it’s not too long until they realize the danger does not lurk outside in the frozen Alaskan tundra, but with their co-workers who are after priceless treasure and will stop at nothing to get it. Fans of Longmire will thrill to this pulse-pounding and bone-chilling novel of extreme adventure that adds another indelible chapter to the great story of Walt Longmire.